2019
DOI: 10.1136/bmjopen-2019-033846
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between visual acuity and muscle mass in the Korean older population: a cross-sectional study using Korean National Health and Nutrition Examination Survey

Abstract: ObjectivesWe aimed to assess the effects of visual acuity on muscle mass, which is an important indicator of health in older populations.DesignPooled-sample cross-sectional study.SettingNationally representative population survey data.ParticipantsThe present study analysed men aged 65 years or older who participated in the Korea National Health and Nutrition Examination Survey (KNHANES, 2008–2011).Primary and secondary outcome measuresMuscle mass was measured by dual-energy X-ray absorptiometry scan, and low m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Two studies showed evidence of significant associations between objectively measured sensory impairment parameters and low muscle mass. In a cross‐sectional study of Koreans aged ≥65 years, Moon and colleagues demonstrated that VI was associated with a 1.6‐fold higher odds of low muscle mass (OR 1.60; 95% CI 1.02 to 2.50; P = 0.04) 22 . Similarly, in a longitudinal study of US adults ≥70 years by Purdy and associates, individuals with SI at baseline experienced a greater annual decline in total lean mass (−139 g/year, 95% CI: −236 to −43; P < 0.05) compared with those without SI at baseline 32 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies showed evidence of significant associations between objectively measured sensory impairment parameters and low muscle mass. In a cross‐sectional study of Koreans aged ≥65 years, Moon and colleagues demonstrated that VI was associated with a 1.6‐fold higher odds of low muscle mass (OR 1.60; 95% CI 1.02 to 2.50; P = 0.04) 22 . Similarly, in a longitudinal study of US adults ≥70 years by Purdy and associates, individuals with SI at baseline experienced a greater annual decline in total lean mass (−139 g/year, 95% CI: −236 to −43; P < 0.05) compared with those without SI at baseline 32 …”
Section: Resultsmentioning
confidence: 99%
“…Given the high prevalence rates of sarcopenia and sensory impairment in older adults, their associations with other geriatric syndromes and the presence of several shared health‐related risk factors 5,14–17 . A direct relationship between the two has been hypothesized 22,23 . Establishing this relationship is important, as sensory impairments can be managed effectively with sensory interventions such as cataract surgery, provision of glasses and hearing aids, and olfactory management 24–27 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On upper facial expression, namely AU 06 and 07, the older adults can show greater intensity than the younger adults. Increased activity in orbicularis oculi muscle [ 81 ], deeply set of eye [ 82 ], and changes in eyelid due to poor visual acuity [ 83 ] may have affected the changes in upper facial expression. For lower facial expression, AU 10, 12, 14, the strength of the face may have been further tapped due to the highlighted facial contour caused by loss of subcutaneous fill around the nose and mouth in the older adults [ 84 ].…”
Section: Discussionmentioning
confidence: 99%